Evolutionary Dynamics of wAu-Like Wolbachia Variants in Neotropical Drosophila spp. - Miller, Wolfgang J. (American Society for Microbiology, 2006)
Wolbachia bacteria are common intracellular symbionts of arthropods and have been extensively studied in Drosophila. Most research focuses on two Old Word hosts, Drosophila melanogaster and Drosophila simulans, and does not take into account that some of the Wolbachia associations in these species may have evolved only after their fast global expansion and after the exposure to Wolbachia of previously isolated habitats. Here we looked at Wolbachia of Neotropical Drosophila species. Seventy-one lines of 16 Neotropical Drosophila species sampled in different regions and at different time points were analyzed. Wolbachia is absent in lines of Drosophila willistoni collected before the 1970s, but more recent samples are infected with a strain designated wWil. Wolbachia is absent in all other species of the willistoni group. Polymorphic wWil-related strains were detected in some saltans group species, with D. septentriosaltans being coinfected with at least four variants. Based on wsp and ftsZ sequence data, wWil of D. willistoni is identical to wAu, a strain isolated from D. simulans, but can be discriminated when using a polymorphic minisatellite marker. In contrast to wAu, which infects both germ line and somatic tissues of D. simulans, wWil is found exclusively in the primordial germ line cells of D. willistoni embryos. We report on a pool of closely related Wolbachia strains in Neotropical Drosophila species as a potential source for the wAu strain in D. simulans. Possible evolutionary scenarios reconstructing the infection history of wAu-like Wolbachia in Neotropical Drosophila species and the Old World species D. simulans are discussed.